Butterfly-like micro air vehicle - Yang, Xiaobin (2018)
Butterfly cannot hover, but it has unique aerodynamic characteristics such as undulating body motion and low wing loading. Development of flapping wing micro air vehicle is mainly focus on the hovering birds and inserts. Little attention received for butterfly-like micro air vehicle(MAV). In this report, the objective of the project is to develop a power forward flight butterfly-like micro air vehicle with a tail to control the pitch angle. In this report, the author would discuss the detailed design specification and fabrication process of the butterfly-like MAV. Dynamic tests were conducted on a force cell and with a high-speed camera to record the motion of flapping wing, four sets of thrust and power in different frequency would be obtained, compared, and concluded. A conclusion would be draw and future work will be recommended as well.